Corporatist governance in Hong Kong: the case of the sports and arts functional constituency - Yeung, Rikkie L. K.; Kwok, James Y.C.; Chiu, Francesca T.C. (2017)
Hong Kong's semi-democratic system is rooted in corporatist traditions. The selection of the Chief Executive of the Hong Kong Special Administrative Region and the formation of 50% of the Legislative Council are based on functional constituencies (FCs). The FC system manifests corporatism and is often criticised as violating democratic principles. This article examines the design and the patterns of registered voters of the sports and arts functional constituency in order to understand how corporatism operates and distorts the electoral system, as well as how it affects the development of the policy sectors concerned. The findings suggest that the FC system is at odds with the constitutional intent of achieving balanced political participation of all sectors of society. - Reproduced.
Keywords: Sports; Public administration